Uncovering the repertoire of fungal secondary metabolites: From Fleming's laboratory to the International Space Station. Issue 1 (1st January 2018) - Boruta, Tomasz
ABSTRACT: Fungi produce a variety of secondary metabolites (SMs), low-molecular weight compounds associated with many potentially useful biologic activities. The examples of biotechnologically relevant fungal metabolites include penicillin, a β-lactam antibiotic, and lovastatin, a cholesterol-lowering drug. The discovery of pharmaceutical lead compounds within the microbial metabolic pools relies on the selection and biochemical characterization of promising strains. Not all SMs are produced under standard cultivation conditions, hence the uncovering of chemical potential of investigated strains often requires the use of induction strategies to awake the associated biosynthetic genes. Triggering the secondary metabolic pathways can be achieved through the variation of cultivation conditions and growth media composition. The alternative strategy is to use genetic engineering to activate the respective genomic segments, e.g. by the manipulation of regulators or chromatin-modifying enzymes. Recently, whole-genome sequencing of several fungi isolated from the Chernobyl accident area was reported by Singh et al. (Genome Announc 2017; 5:e01602–16). These strains were selected for exposure to microgravity at the International Space Station. Biochemical characterization of fungi cultivated under extreme conditions is likely to provide valuable insights into the adaptation mechanism associated with metabolism and, possibly, a catalog of novel molecules of potential pharmaceutical importance.